False Reality: Deepfakes in Terrorist Propaganda and Recruitment - Al Waro'i, Muhammad Nur Abdul Latif (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
Deepfake technology, which leverages artificial intelligence to create hyper-realistic digital fabrications, has emerged as a significant threat across various domains, notably in terrorism. This review critically examines the exploitation of deepfakes in terrorist propaganda and recruitment, presenting a systematic analysis of the technical mechanisms behind their creation and detection, historical and contemporary propaganda methods, and their psychological impacts on audiences. The study identifies key advancements in deepfake detection technologies, such as ensemble learning and convolutional neural networks, which are crucial in distinguishing real from synthetic media. Furthermore, the review highlights the importance of public awareness and psychological resilience as vital countermeasures against deepfake manipulation. Despite technological advancements, significant challenges remain, including the development of real-time detection systems capable of operating in diverse and uncontrolled environments and a comprehensive understanding of the psychological processes affected by deepfake propaganda. The review underscores the urgent need for robust policy frameworks and international cooperation to address the ethical, legal, and security implications of deepfake technology. By integrating technical, psychological, and policy perspectives, this study provides a holistic understanding of deepfake technology's role in modern terrorism and offers insights for developing effective countermeasures. The comprehensive approach aims to contribute to the creation of robust strategies to mitigate the misuse of deepfake technology, ensuring a safer and more trustworthy digital environment.